L-shaped association of body mass index with prognosis in individuals with sepsis: a multicenter cohort study - Kunping Cui; Xiangnan Teng; Wei liu; Xiaoxiao Zhao; Shanling Xu; Lang Bai (Diabetology & Metabolic Syndrome)
Abstract Objective The relationship between body mass index (BMI) and sepsis prognosis remains highly controversial and uncertain. This study investigated the association between BMI and prognosis in patients with sepsis. Methods This retrospective observational cohort study included adult patients admitted to the intensive care unit (ICU) with sepsis from Medical Information Mart for Intensive Care-IV version 2.2 (MIMIC-IV V2.2) and eICU Collaborative Research Database (eICU-CRD). The cut-off value of BMI was identified by the restricted cubic spline (RCS) curve and included patients were categorized into two groups: the low BMI group (< 28 kg/m2) and the high BMI group (≥ 28 kg/m2). The primary outcome was ICU mortality, and secondary outcomes were in-hospital and 28-day mortality. We performed the log-rank test to detect whether there is a difference in prognosis among different groups in two different cohorts. Multiple distinct models were used to validate the robustness of the results. Results There were 18,385 and 38,713 patients in the MIMIC-IV 2.2 and eICU-CRD cohorts, respectively. An L-shaped relationship was observed between BMI and ICU mortality in the primary analysis from MIMIC-IV 2.2. Similar relationships were found in eICU-CRD. When BMI was less than the cut-point, the risk of ICU mortality increased rapidly with decreasing BMI. When BMI was greater than the cut-point, the risk of ICU mortality levelled off as BMI increased. Sepsis patients with higher BMI values exhibited decreased ICU all-cause mortality rates (MIMIC-IV cohort: HR: 0.81, 95% CI 0.75–0.88, p < 0.001; eICU-CRD cohort: HR: 0.75, 95% CI 0.71–0.80, p < 0.001). Consistent trends were observed for both in-hospital mortality and 28-day mortality rates. The results remained robust in multiple distinct models and subgroup analyses. Conclusion An L-shaped relationship was observed between BMI and prognosis in septic patients, indicating that lower BMI values are significantly linked to increased mortality. Targeted nutritional interventions and close monitoring for patients with low BMI could potentially enhance their prognosis. Therefore, BMI can also be utilized to categorize the risk levels of patients with sepsis and effectively predict their prognosis.